Examining Technical, Human-Social, and Methodological Influences on K-Worker Competency: A Comparative Analysis of Experienced vs. Novice Economics Students at Telkom University - Iman Santoso, Teguh; Galuh Tresna Murti; Moch Aminudin Hadi; Muhammad Nurwaskita Alamsyah (APMBA (Asia Pacific Management and Business Application), 2025)
The Indonesian labor market faces a significant and persistent skills gap, particularly among knowledge-intensive industries, where Knowledge-workers require specialized competencies. This study seeks to address this gap by examining the roles of technical, human-social, and methodological competencies in enhancing K-worker preparedness among economics students at Telkom University. A cross-sectional survey of 1,401 students evaluates the impact of these competencies and explores how previous work experience affects competency development. Results reveal that each competency—technical, human-social, and methodological—meaningfully contributes to overall Knowledge-worker readiness, with technical skills emerging as the most influential factor in job preparedness. Surprisingly, work experience does not strongly moderate these competency impacts, highlighting that foundational skill development within the curriculum remains paramount for fostering employability. These findings emphasize the need for competency-based education frameworks that prioritize foundational skills to meet the ASEAN labor market's demands. The study provides actionable insights for higher education policymakers and curriculum designers in Indonesia, suggesting that a stronger focus on comprehensive competency-based training can better equip graduates for competitive regional workforce integration. Continuous professional development initiatives are also highlighted as crucial, enabling graduates to adapt and grow in their careers. This research contributes to ongoing discussions on bridging educational outcomes with industry needs and reinforces the role of curriculum reform in promoting workforce competitiveness across Southeast Asia.